Night of the jaguar - Gruber, Michael, 1940- (Gruber, Michael, 1940- Jimmy Paz series., 2007)
Retired Miami Homicide Detective Jimmy Paz has put the darkness behind him. But now he, his wife, and their young daughter are being haunted by terrifying dreams. And when affluent Miami businessmen begin dying gruesomely in their fortress-like homes--with the footprints of a giant jungle cat found at the crime scenes--Paz has no choice but to get involved, because what he loves most may be the next thing devoured. From the acclaimed author of Tropic of Night, Valley of Bones, The Book of Air and Shadows, and The Forgery of Venus comes the final book in his masterful Jimmy Paz series, hailed by the Washington Post as a "miracle of intelligent fiction ... among the essential novels of recent years."